Exploring the Impact of Media Content on Social Media Engagement Through Comment Analysis - Airi, Lal Bahadur; Bhattarai, Shiva Prasad (Baneshwor Campus Journal of Academia, 2024)
This study investigates audience participation on the social media platforms of Kantipur Daily, Sagarmatha Radio, and Nepal Television using survey data collected in 2024. A review of comments on Facebook and X(Twitter) indicated that positive feedback is primarily focused on sports and social/health/lifestyle news Moreover, opinions and economic news receive relatively less attention than political news. The study highlights particular areas that need more research and offers insightful information about audience dynamics in the context of digital communication. This finding emphasizes the value of social media as a political communication tool, which is especially clear from the positive comments on Political News. Additionally, despite certain restrictions, the results show how the communication landscape is changing and how social media is improving news accessibility and content quality. The finding indicates that social media has become a new arena for public affairs, and its results show that Facebook is more widely used than X.